Clinical phenotype in patients with α-synuclein Parkinson's disease living in Greece in comparison with patients with sporadic Parkinson's disease. Issue 5 (1st May 2001) - Papapetropoulos, S; Paschalis, C; Athanassiadou, A; Papadimitriou, A; Ellul, J; Polymeropoulos, M H; Papapetropoulos, Th
Abstract : OBJECTIVE: An Ala53Thr mutation of the α-synuclein gene has been recently identified as a rare cause of autosomal Parkinson's disease (PD). The clinical characteristics of 15 patients with PD living in Greece with the Ala53Thr α-synuclein mutation (α-synPD) were compared with patients with sporadic Parkinson's disease (sPD). METHODS: An investigator, blind to the results of the genetic analysis, examined 15 patients with α-synPD and 52 consecutive patients with sPD. Demographic data, age at onset of the illness, modality of presentation, and duration of PD were collected. The unified Parkinson's disease rating scale, the Hoehn and Yahr scale, and the Schwab-England scale were completed. The patients with α-synPD were matched for duration of disease with 32 of the 52 patients with sporadic PD (MsPD group). RESULTS: Patients with the α-synuclein mutation were significantly younger (mean 7.6 years), showed the first sign of the disease significantly earlier in life (mean 10.8 years), and had significantly longer duration of the disease compared with patients with sPD. Tremor at onset of the disease was present in only one (6.7%) of the patients with α-synPD, whereas it was present in 32 (61.5%) of the patients with sPD (p=0.0006). During the course of the disease one patient in the α-synPD group went on to develop tremor compared with six patients in the sPD group. Rigidity, bradykinesia, postural instability, orthostatic hypotension, intellectual impairment, depression, complications of therapy, and clinical severity of the disease at the time of examination did not differ significantly between patients with α-synPD and those with sPD, or between patients with α-synPD and the MsPD group. CONCLUSION: The younger age at onset of the illness, the much lower prevalence of tremor, and the longer duration of the disease characterise the clinical phenotype in this sample of patients with α-synPD. The other symptoms and signs of the illness did not seem to differentiate the patients with α-synPD from those with sPD.